2019
DOI: 10.5194/os-15-235-2019
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of air–sea gas transfer velocities in the Baltic Sea

Abstract: Abstract. Heat transfer velocities measured during three different campaigns in the Baltic Sea using the active controlled flux technique (ACFT) with wind speeds ranging from 5.3 to 14.8 m s−1 are presented. Careful scaling of the heat transfer velocities to gas transfer velocities using Schmidt number exponents measured in a laboratory study allows us to compare the measured transfer velocities to existing gas transfer velocity parameterizations, which use wind speed as the controlling parameter. The measured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…They suggested that K 660 should be scaled with Sc -2/3 within this smooth regime; then once waves appear the Schmidt number exponent transitions to -1/2. Recent laboratory (Nagel et al, 2019) and field (Esters et al, 2017) observations imply that there is a smooth transition in n between -2/3 and -1/2. The intercepts of the K 660 -u * fits (over u * range of 0.1-0.5 m s -1 ) are negative for all cruises (Table 2), which implies different physical processes occurring at low wind speeds.…”
Section: Low Wind Regimementioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that K 660 should be scaled with Sc -2/3 within this smooth regime; then once waves appear the Schmidt number exponent transitions to -1/2. Recent laboratory (Nagel et al, 2019) and field (Esters et al, 2017) observations imply that there is a smooth transition in n between -2/3 and -1/2. The intercepts of the K 660 -u * fits (over u * range of 0.1-0.5 m s -1 ) are negative for all cruises (Table 2), which implies different physical processes occurring at low wind speeds.…”
Section: Low Wind Regimementioning
confidence: 99%
“…3 He and SF 6 differ from CO 2 from at least two perspectives: 1) they are much less soluble than CO 2 , and solubility is important in bubble-mediated gas exchange (Woolf, 1997;Asher and Wanninkhof, 1998); 2) they are inert, whereas the air-sea exchange of CO 2 is affected by chemical enhancement due to the carbonate kinetics (Wanninkhof, 1992). In addition, the derivation of K 660 from the 3 He/SF 6 measurements is highly sensitive to the Schmidt number exponent n, which is thought to deviate from -1/2 at low wind speeds (e.g., Esters et al, 2017;Nagel et al, 2019). It is arguably more robust to use K 660 directly derived from CO 2 measurements to estimate the global/regional CO 2 flux to avoid the aforementioned possible sources of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic view of the resistances for bubble-mediated gas transfer R c = k −1 c in relation to the air- and water-sided resistances for transfer through the unbroken water surface. Many approaches have been made to quantify the bubblemediated gas transfer k c : gas transfer by single bubbles (Maiß, 1986;Patro et al, 2002), transfer in bubble clouds (Asher et al, 1996;Mischler, 2014) and breaking waves (Asher et al, 1995;Leifer and De Leeuw, 2002), as well as theoretical models based on bubble dynamics (Memery and Merlivat, 1985;Woolf and Thorpe, 1991). Bubble-mediated gas transfer also depends on bubble surface conditions.…”
Section: Bubble-mediated Gas Transfermentioning
confidence: 99%
“…Bubble-mediated gas transfer also depends on bubble surface conditions. It has been shown that surface active material reduces the gas transfer of single bubbles (Maiß, 1986;Patro et al, 2002), while it also decreases the bubbles' rise velocity (Alves et al, 2005). During the lifetime of a bubble, these surface conditions can change, as bubbles accumulate surface active material while moving through the water.…”
Section: Bubble-mediated Gas Transfermentioning
confidence: 99%
“…The influence of fetch and thus waves on gas transfer has so far only been studied at wind speeds of less than 10 m s −1 and proved to be only significant at wind speeds lower than 6 m s −1 (Kunz and Jähne, 2018). However, recent measurements in the Baltic Sea using active thermography also showed large variations in the gas transfer velocity at wind speeds higher than 10 m s −1 , which is most likely related to the effect of surfactants (Nagel et al, 2019).…”
Section: Dimethyl Sulfide and Carbon Dioxidementioning
confidence: 99%